Cyberpragmatic Strategies in Netizen Commentaries on a Viral Indonesian Infidelity Case at TikTok - Mezia Kemala Sari; Beny Hamdani; Faizal Risdianto; Erlinda Syam; Suci Rahmah Safitunnajah (JADEs Journal of Academia in English Education, 2026)
This study examines how Indonesian netizens employ cyberpragmatic strategies in responding to a viral infidelity confession circulated on TikTok in early 2025. Drawing on a qualitative cyberpragmatic framework, the study analyzes 100 purposively selected user comments to explore how emotional expression, social alignment, and moral judgment are pragmatically negotiated in digitally mediated interaction. The findings show that venting, solidarity, and cyberbullying emerge as three dominant and interconnected strategies. Venting functions as a form of digital catharsis, realized through emotional storytelling, sarcasm, and informal linguistic and multimodal resources that transform private trauma into shared public narratives. Solidarity is enacted through empathetic and advisory responses that foster collective learning and gendered support, while cyberbullying manifests in verbal aggression and victim-blaming that reproduce patriarchal moral judgment. Rather than treating these practices as isolated forms of online behavior, this study argues that venting, solidarity, and cyberbullying operate as interconnected cyberpragmatic strategies shaped by TikTok’s affordances of anonymity, a synchronicity, and multimodality.